MEDIA SOSIAL SEBAGAI ARENA KONSTRUKSI SOLIDARITAS KEAGAMAAN: STUDI PUSTAKA TENTANG KOMUNIKASI DAN PENYIARAN ISLAM DI RUANG DIGITAL - Ulfain; Saputra, Moh Guntur (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
The presence of social media in the lives of contemporary Muslims has opened a new dimension in the dynamics of religious communication, which has traditionally relied on physical gatherings and traditional institutions. Digital platforms such as Instagram, Twitter/X, Facebook, YouTube, and Telegram are no longer merely tools for entertainment or general information, but have transformed into arenas where religious solidarity is produced, negotiated, and reinforced on a daily basis. This phenomenon has attracted serious attention from scholars of Islamic communication, as it has the potential to fundamentally reshape how Muslims build a sense of togetherness, compassion, and collective identity as a faith community. This study aims to systematically examine how social media functions as an arena for constructing religious solidarity from the perspective of Islamic communication and broadcasting. The method used is a systematic literature review of scientific sources, including books and reputable journals published within the last five years. The findings reveal three main mechanisms in the construction of religious solidarity on social media: the practice of sharing content based on shared Islamic values, the formation of digital affective communities that transcend geographical boundaries, and collective mobilization based on digital religious symbols.This research contributes to the development of a theoretical framework in Islamic communication and broadcasting that can more comprehensively explain the phenomenon of digital religious solidarity and remain relevant to the context of Muslim societies in the 21st century